Death in the stacks - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries., 2017)
"In the latest Library Lover's Mystery from the New York Times bestselling author of Better Late Than Never, the library's big fund-raiser leaves director Lindsey Norris booked for trouble. Lindsey Norris and her staff are gearing up for the Briar Creek Library's annual Dinner in the Stacks fund-raiser. The night of dinner and dancing is not only a booklover's dream--it's the library's biggest moneymaker of the year. But instead of raising funds, the new library board president is busy raising a stink and making the staff miserable. Although Olive Boyle acts like a storybook villain, Lindsey is determined to work with her and make the event a success. But when Olive publicly threatens the library's newest hire, Paula, Lindsey cracks like an old book spine and throws Olive out of the library. The night of the fund-raiser, Lindsey dreads another altercation with Olive--but instead finds Paula crouched over Olive's dead body. Paula may have secrets, but Lindsey and the rest of the crafternooners know she's not the one who took Olive out of circulation. As the plot thickens, Lindsey must catch the real killer before the book closes on Paula's future"--